European Bifurcation Club white paper on stenting techniques for patients with bifurcated coronary artery lesions. Issue 5 (24th June 2020) - Burzotta, Francesco; Lassen, Jens Flensted; Louvard, Yves; Lefèvre, Thierry; Banning, Adrian P.; Daremont, Olivier; Pan, Manuel; Hildick‐Smith, David; Chieffo, Alaide; Chatzizisis, Yiannis S.; Džavík, Vladimír; Gwon, Hyeon‐Cheol; et al.
Abstract: Background: Defining the optimal conduction of percutaneous‐coronary‐intervention (PCI) to treat bifurcation lesions has been the subject of many clinical studies showing that the applied stenting technique may influence clinical outcome. Accordingly, bifurcation stenting classifications and technical sequences should be standardized to allow proper reporting and comparison. Methods: The European Bifurcation Club (EBC) is a multidisciplinary group dedicated to optimize the treatment of bifurcations and previously created a classification of bifurcation stenting techniques that is based on the first stent implantation site. Since some techniques have been abandoned, others have been refined and dedicated devices became available, EBC promoted an international task force aimed at updating the classification of bifurcation stenting techniques as well as at highlighting the best practices for most popular techniques. Original descriptive images obtained by drawings, bench tests and micro‐computed‐tomographic reconstructions have been created in order to serve as tutorials in both procedure reporting and clinical practice. Results: An updated Main‐Across‐Distal‐Side (MADS)‐2, classification of bifurcation stenting techniques has been realized and is reported in the present article allowing standardized procedure reporting in both clinical practice and scientific studies. The EBC‐promoted task force deeply discussed, agreed on and described (using original drawings and bench tests) the optimal steps for the following major bifurcation stenting techniques: (a) 1‐stent techniques ("provisional" and "inverted provisional") and (b) 2‐stent techniques ("T/TAP, " "culotte, " and "DK‐crush"). Conclusions: The present EBC‐promoted paper is intended to facilitate technique selection, reporting and performance for PCI on bifurcated lesions during daily clinical practice.